2021
DOI: 10.1093/annweh/wxaa108
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Skin and Respiratory Exposure to Lufenuron During Spraying and Re-entry in Italian Ornamental Plants Greenhouses

Abstract: The aim of this study was to evaluate dermal and respiratory exposure of workers to Lufenuron during spraying and re-entry on ornamental plants (stapling) in greenhouses. Potential and real skin exposure were evaluated using filter paper pads, hand contamination by washing, and respiratory exposure by personal air sampling. Dislodgeable foliar residues (DFRs) during re-entry were determined in order to calculate the dermal transfer factor (DTF). Lufenuron was analysed by liquid chromatography–mass detection. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As a result, some chemicals from the pesticides can penetrate through the skin ( 19 ). A study by Aprea et al ( 30 ) which investigated skin and respiratory exposure during spraying of lufenuron and re-entry in ornamental plant greenhouses suggested that the dose absorbed ranged from 0.144–0.171 and 0.005–0.124 μg/kg body weight during spraying and stapling, respectively, and the respiratory dose ranged from 68.7–74.6 and 0.022–0.636% of the total real dose during spraying and stapling, respectively. They also suggested that appropriate use of PPE and equipment was the fundamental aspect in reducing pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, some chemicals from the pesticides can penetrate through the skin ( 19 ). A study by Aprea et al ( 30 ) which investigated skin and respiratory exposure during spraying of lufenuron and re-entry in ornamental plant greenhouses suggested that the dose absorbed ranged from 0.144–0.171 and 0.005–0.124 μg/kg body weight during spraying and stapling, respectively, and the respiratory dose ranged from 68.7–74.6 and 0.022–0.636% of the total real dose during spraying and stapling, respectively. They also suggested that appropriate use of PPE and equipment was the fundamental aspect in reducing pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the topic of exposure of workers in the sector across the chain of flower production to market, has received some attention in past decade (Morse et al, 1979;Carlile, 2006;Lu and Cosca, 2011;Enserink et al 2013;Stanley and Raine, 2016;Mengistie et al, 2017;Brouwer et al, 2010;Toumi et al, 2016a;Toumi et al, 2018;Shentema et al, 2020;Nassar and Ribeiro, 2020;Aprea et al, 2021). Different studies conclude problems causing the workers' feet to swell due to standing for many hours in the greenhouse, kidney problems headaches, coughing, skin rushes, respiratory problems, blood vein problems, pneumonia, bronchitis, sinus, vomiting and others (Mekonnen and Agonafir 2002;Negatu et al 2016;Mengistie et al, 2016;Mengistie et al, 2017) and poorer neurobehavioral development, reproductive disorders, congenital malformations and genotoxicity have been reported for residents of flower production areas and workers throughout the flower production cycle (Pereira et al, 2021).…”
Section: Identification Of Pesticide Residues Through Molecular Vibra...mentioning
confidence: 99%